Hubungan Cyberloafing Behavior Dengan Organizational Commitment Pada Pegawai Di Puskesmas - FEBRIYANTI NURSYA; Nurul Prihastita Rizyana (JURNAL KESEHATAN MERCUSUAR, 2023)
Health centers are one of the important service aspects for the community. All employees who work at the health center must always be ready to provide the best service starting from doctors, nurses, administrative staff, pharmacists, and cleaning services. Cyberloafing behavior is categorized as disciplinary behavior, the division of employee concentration between work and cyberloafing behavior has an impact on piling up work, low work productivity, poor work quality, can interfere with the smooth work process and slow public services so that it will have a negative impact on the image of the organization. In the process, good organizational commitment is needed so that a puskesmas goal of serving patients maximally can be achieved by reducing deviant behaviors that exist in organizations such as cyberloafing behavior. This research is a quantitative study using a cross sectional study design. With the dependent variable being organizational commitment while the independent variable is cyberloafing behavior. The research was conducted in June 2023 at one of the health centers in Padang City. The population and sample of this study were all employees totaling 49 people using a questionnaire instrument. Data were analyzed univariately by looking at the frequency distribution table and bivariate analysis using the ChiSquare test.Based on the results of the research conducted, almost half of the respondents did cyberloafing behavior and more than half of the respondents had employee commitment. The statistical test results obtained p = 0.023, meaning that there is a significant relationship between cyberloafing behavior and organizational commitment It is recommended that the Puskesmas begin to socialize the impact of cyberloafing behavior in daily employee work activities.